Platform for Educational Games Generation - André Gomes Barbosa (2015)
The development of games for education is a growing area of research. Over the past few years, studies point out that the use of games as a supplement to traditional learning is much more efficient and motivational than just using the traditional teaching method. These are called serious games. This work aims to extend and improve a previous game developed to learn software testing as the contents of the game are loaded from a XML file which would be separated from the game implementation. The game itself, iLearnTest, consists of several challenges which cover various themes regarding software testing learning.Since the content is saved to and loaded from a separate file from the game implementation, it becomes easier to create and edit new levels or even new games for diferent topics, simply by editing a XML file. This new approach turns iLearnTest into a framework rather than a game in the sense that it is possible to use the same game(s) as templates for the learning process of a variety of themes.